Стан охорони праці на підприємствах м'ясоперобної промисловості України - Євтушенко, Ольга Володимирівна; Коваленко, Сергій Дмитрович (НУХТ, 2013)
У статті розглянуто сучасний стан охорони праці на підприємствах м'ясопереробної промисловості. Визначено фактори виникнення травм. Найбільш небезпечними на м'ясопереробному підприємстві є професії: забійника худоби, вантажника, слюсаря-ремонтника та оброблювача туш. Порівняльна оцінка результатів прогнозу на 2012 рік зі статистикою виробничого травматизму за 2012 рік показала, що середня достовірність прогнозу склала 85,37 %. Результати дослідження можна використати при вдосконаленні проектів управлінських рішень щодо забезпечення безпечних умов праці працівників м'ясопереробних підприємств. The article discusses the current state of labor protection in enterprises meat industry. The causes of injuries were determined. The most traumatic professions on Meat Processing Plant are butcher, loader, locksmith, handler of brawn. Dynamics of butcher injuries which is described by exponential function is increasing. Dynamics of loader injuries is described by third-degree polynomial. Dynamics of handler of brawn injuries is changing with acceleration and is described by fifth-degree polynomial. Dynamics of locksmith injuries is described by the fourth-degree polynomial. Comparative estimation of prediction results for 2012 with statistics of occupational injuries for 2012 showed that average authenticity of prediction is 85,37%. Results of research can be used in improving management decisions projects that can provide safe working conditions on Meat Processing Plants.
Keywords: безпека; праця; травматизм; ризик; нещасний випадок; safety; work injuries; risk; accident; кафедра екології та екоменеджменту